(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: Acute bronchiolitis is a viral respiratory illness of infants and young children. It is characterized by coryzal symptoms followed by rapid onset of cough, wheeze, fever, tachypnea, chest recession and crepitation with radiological evidence of hyperinflation. Bronchiolitis occurs in first 2 years of age and is usually caused by respiratory syncytial virus. Objective: To find out the effectiveness of antibiotic in treatment of bronchiolitis. Methods: It was a randomized controlled trial carried out in Department of Paediatrics, Rajshahi Medical College Hospital, Rajshahi. 200 acute bronchiohtis patient admitted into paediatric ward of Rajshahi Medical College Hospital who fulfill inclusion criteria. Then relevant history and physical examination findings were recorded in data sheet. The even numbered patient was selected as control group and odd numbered patients as intervention group. The control group was receive supportive management and intervention group was receive lnj. Ceftriaxone 75mg/kg/day in for 5 days along with supportive management. Results: This study it was observed that bronchiolitis was more common in male. The age for peak incidence (75%) of bronchiolitis was 2-6 months. About 59% children presented with fever and all of them recovered from fever quickly before leaving hospital. At the time of admission 43% children had feeding difficulty, which improved steadily and similarly in both the groups. For days hours after admission 16% of antibiotic group and 15% of without antibiotic group had similar chest indrawing. Cough was the most common starting symptoms. None of the cases showed cyanosis and at the time of admission total 91% children had SpO2 <95%, after 4 days of admission 33%of antibiotic group and 14% of without antibiotic group still had SpO2 <95% but during discharge none of them had hypoxia. After 4 days of admission 17% of antibiotic group and 14% of without antibiotic group had crepitation and 6 days after discharge 1(1%) child of without antibiotic group and 2(2%) from antibiotic group still had crepitation. It was observed that hypertranslucency in 74% and hyperinflation in 64% in cases. Conclusion: This study shows antibiotics have no role in acute bronchiolitis management. Further multicenter study with larger sample size is recommended. TAJ 2013; 26: 43-47